Diagnostic accuracy and utility of The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC), 2017 in an Indian Scenario: A tertiary care appraisal - Sujata Raychaudhuri; Dipti Sidam; Ruchira Wadhwa; Kanika Singh; Mukta Pujani; R.K. Chandoke (Al Ameen Medical College, 2024)
Objective: To categorize the cytological pattern according to Bethesda System for Reporting Thyroid Cytopathology and correlate them with the histopathological diagnosis. Calculate the sensitivity, specificity, accuracy of thyroid lesions and also the risk of malignancy in each category. Material &Methods: A retrospective re- evaluation of all consecutive thyroid fine-needle aspiration cytology fine-needle aspiration cytology smears was done from 2016 to 2019. Results: 429 patients were subjected to fine-needle aspiration cytology while histopathology was available for 109 cases. The sensitivity was 84.6% and specificity was96.4% with accuracy of 93.6%. The risk of malignancy for categories I, II, III, IV, V and VI was 0%, 1.4%, 20%, 20%, 100% and 100% respectively. Conclusion: The study shows application of Bethesda System for Reporting Thyroid Cytopathology in a tertiary care centre in a developing country is a successful step to bring about uniformity and standardise thyroid cytology reporting by reducing the ambiguity.